Comparison of the Trucut and Surecut liver biopsy needles. Issue 7 (July 1982) - Littlewood, E R; Gilmore, I T; Murray-Lyon, I M; Stephens, K R; Paradinas, F J
Abstract : The Trucut and Surecut liver biopsy needles have been compared in a prospective randomised study. Although the Surecut specimens were longer and heavier they tended to fragment during processing. Trucut specimens were subject to less artefact and were rated more highly by the histopathologist. However, the majority of biopsies obtained by both needles were satisfactory for diagnostic purposes.